Penggunaan Collocation dalam Meningkatkan Kemampuan Keluasan Kosakata (Vocabulary Breadth) Bahasa Inggris Mahasiswa Pariwisata di AKPAR Mataram - Tri Dharma, I Nyoman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The purpose of this study was to determine the effect of using collocation to improve students’ English vocabulary breadth of Akpar Mataram hospitality students. Researcher take 50 students as sample. This study used a quasi-experimental research model with one group pre-test and post-test research design. Based on the result of the t-test paired sample test which calculated with SPSS, it was obtained that the result showed the sig. value (2-tailed) was 0.000 with 5% probability. The sig. value is smaller than 0.005. So it can be said that there is an effect of using collocation to improve students’ vocabulary of AKPAR Mataram.